Modeling of a tubular permanent magnet linear generator for wave energy conversion using finite element method - Hamim, M.A.F.M. (IEEE Computer Society, 2014)
This paper presents the modeling process of a tubular permanent magnet linear generator for the wave energy conversion system. Two types of linear generator technology namely the planar and tubular with different on translator, stator and magnet arrangement are identified but due to the high detent force, low flux density and high fabrication cost, tubular excogitation is preferable. Three linear permanent magnet generators with different types of permanent magnet layout have been proposed. Preliminary results for the number of turns and varying speed proportional with induced voltage and open circuit test are demonstrated and discussed are shown to be as expected. Based on the overall findings, the shape of permanent magnet in the excogitation affects the performance of the generator. Â© 2014 IEEE.